Retrograde percutaneous recannalisation of chronic total occlusion of the coronary arteries: procedural outcomes and predictors of success in contemporary practice. (22nd September 2015) - Rathore, S; Katoh, O; Matsuo, H; Terashima, M; Tanaka, N; Kinoshita, Y; Kimura, M; Tsuchikane, E; Nasu, K; Asakura, K; Ehara, M; Asakura, Y; et al.
Abstract : Background: The retrograde approach is being increasingly used for recanalisation of chronic total occlusion (CTO) in the event of failed antegrade attempt or unsuitable CTO anatomy. There is no literature about predictors of success and failure using the retrograde approach in contemporary practice. Objective: To define the predictors of success and failure using the retrograde approach for CTO percutaneous coronary intervention (PCI). Methods: We studied 157 consecutive patients who underwent retrograde CTO PCI between 2003 and 2008, and compared the successful (103 patients) and failed (54 patients) attempts. Results: Procedural success was achieved by the retrograde approach in 65.6% of the patients. Baseline characteristics were similar in both groups, and angiographic characteristics, including severe calcification, aorto-ostial location, severe tortuosity, bridging collaterals and CTO length, were similar in both groups (16.7%, 1.9%, 13.0%, 22.2%, 34.76 ± 16.83 mm vs 13.6%, 2.9%, 13.6%, 25.2%, 37.15 ± 18.84 mm, p = ns, in failure and success groups, respectively). CTO vessel was similar in both groups (right coronary artery: 51.9 vs 62.1%; left anterior descending 38.9 vs 28.2; left circumflex 9.3 vs 6.8; left main stem 0 vs 1; saphenous vein graft (SVG) 0 vs 1, p = 0.582, in failure and success groups, respectively). Septal, epicardial and SVG collaterals were used in 67.5%, 24.8% and 7.6% cases, respectively. Retrograde channel properties influenced the outcome in the majority of patients. CC type 1, collateral tortuosity less than 90 degrees, and angle with recipient vessel less than 90 degrees (p<0.0001) are significant predictors of success. Whereas epicardial channel use (p = 0.01), CC type 0, corkscrew channel (p<0.0001), angle with recipient vessel greater than 90 degrees (p = 0.0007) and non-visibility of connection with recipient vessel were found to be significant predictors of procedural failure. The collateral channel dissection was observed in five patients, with one needing coil embolisation and others were managed conservatively. The MACE events were low, with one coronary artery bypass grafting, one Q-wave myocardial infarction, five non-Q-wave myocardial infarctions and no deaths in this group of patients. Conclusions: The retrograde approach in CTO PCI is effective in recanalising CTO in previously failed antegrade attempts. The success rate by the retrograde approach was 65.6% and final success was 85% with low overall adverse events. Epicardial channel use, CC type 0, corkscrew collateral channel and angle with recipient vessel of greater than 90 degrees were found to be significant predictors of failure by retrograde approach during CTO PCI.